Children and adolescents protection policies in Uruguay. An approach to programs with proximity methodology - Lima Benitez, Victoria (2021)
This article is focused on the analysis of the children and adolescents protection policies in Uruguay. Specifically, on three programs that are aimed at having a focused intervention mode by territorialization, inter-institutionalism and proximity. It will analyze the tensions and challenges of these programs, taking into account whether they generate real transformations in life trajectories or whether they are processes of individualization of poverty. Uruguay’s State has ratified the Convention on the rights of the children and at a nation level is framed under the code of childhood and adolescence, because of this reason the category should be a priority of the political agenda. Considering this, do these children and adolescents protection policies protect them,or is this just a type of tutoring?